Anterior segment optical coherence tomography angle and vault analysis after toric and non-toric implantable collamer lens V4c implantation in patients with high myopia. Issue 4 (20th July 2017) - Garcia-De la Rosa, Guillermo; Olivo-Payne, Andrew; Serna-Ojeda, Juan Carlos; Salazar-Ramos, Maria Sandra; Lichtinger, Alejandro; Gomez-Bastar, Arturo; Ramirez-Miranda, Arturo; Navas, Alejandro; Graue-Hernandez, Enrique O
Abstract : Objective: To assess anterior segment changes, including iridocorneal angle and vault, after toric and non-toric implantable collamer lens (ICL) V4c (STAAR Surgical AG) implantation under different lighting conditions. Methods: Longitudinal, prospective, case series. Patients with high myopia (>6 dioptres) underwent toric and non-toric ICL V4c implantation. Optical coherence tomography measurements were taken under different lighting conditions preoperatively and at 1 week and 1, 6 and 12 months of follow-up. Results: Seventy-six eyes of 42 patients underwent ICL V4c implantation. Mean age was 27.4 years (±5.14 years, range 20 to 39 years). The average iridocorneal angle showed a statistically significant decrease (p<0.05) in all mesopic, scotopic and photopic conditions after 1 week of surgery compared with the preoperative measurements; in mesopic conditions, it decreased 14.1°, in photopic conditions 14.8° and scotopic conditions 13.2°. The angle measurement had a statistically significant change only in mesopic conditions (p=0.01) over the 1-year follow-up. The average vault under mesopic conditions was 0.661±0.21 mm at week 1. The vault measurement change was statistically significant over the 1-year follow-up in mesopic conditions (p=0.01). Refractive results showed a significant improvement in both uncorrected and corrected distance visual acuity (p<0.001). Conclusion: There is a significant reduction in the iridocorneal angle after ICL V4c implantation. Furthermore, there is a change under mesopic conditions in both the iridocorneal angle and vault during long-term follow-up.